A NEW EARLY-RIPENING VARIETY OF GARDEN PEA KUDESNIK 2 - A. G. Besedin; O. V. Putina (Овощи России)
The early-ripening variety of garden pea ‘Kudesnik 2’ was proposed for State Commission for variety trial in 2015 and regarded to be used in the canning industry. The variety was bred at Krymsk Experimental Plant Breeding Station and considered to be used for continued conveyor-like production for further processing technology at canned-food production enterprises.